Lifting Techniques: Why Are We Not Using Evidence To Optimize Movement? - Nicholas B. Washmuth; Abby D. McAfee; C. Scott Bickel (International Journal of Sports Physical Therapy)
Lifting something off the ground is an essential task and lifting is a documented risk factor for low back pain (LBP). The standard lifting techniques are stoop (lifting with your back), squat (lifting with your legs), and semi-squat (midway between stoop and squat). Most clinicians believe the squat technique is optimal; however, training on squat lifting does not prevent LBP and utilizing greater lumbar flexion (i.e. stoop) when lifting is not a risk factor for LBP. The disconnect between what occurs in clinical practice and what the evidence suggests has resulted in ongoing debate. Clinicians must ask the right questions in order to apply the evidence appropriately. A proposed clinical framework of calm tissue down, build tissue up, improve work capacity can be used to determine which lifting technique is optimal for a patient at any given time. When applying this clinical framework, clinicians should consider metabolic, biomechanical, physical stress tolerance, and pain factors in order to address the movement system. For example, stoop lifting is more metabolically efficient and less challenging to the cardiopulmonary system. There may be few biomechanical differences in spinal postures and gross loads on the lumbar spine between stoop, squat, and semi-squat lifting; however, each lift has distinct kinematic patterns that affects muscle activation patterns, and ultimately the movement system. Clinicians must find the optimal dosage of physical stress to address all aspects of the movement system to minimize the risk of injury. There is no universal consensus on the optimal lifting technique which will satisfy every situation; however, there may be a lifting technique that optimizes movement to achieve a specific outcome. The calm tissue down, build tissue up, improve work capacity framework offers an approach to determine the best lifting technique for an individual patient at any give time.